Prolonged maternal separation attenuates BDNF‐ERK signaling correlated with spine formation in the hippocampus during early brain development. Issue 2 (6th March 2017) - Ohta, Ken‐ichi; Suzuki, Shingo; Warita, Katsuhiko; Kaji, Tomohiro; Kusaka, Takashi; Miki, Takanori
Abstract: Maternal separation (MS) is known to affect hippocampal function such as learning and memory, yet the molecular mechanism remains unknown. We hypothesized that these impairments are attributed to abnormities of neural circuit formation by MS, and focused on brain‐derived neurotrophic factor (BDNF) as key factor because BDNF signaling has an essential role in synapse formation during early brain development. Using rat offspring exposed to MS for 6 h/day during postnatal days (PD) 2–20, we estimated BDNF signaling in the hippocampus during brain development. Our results show that MS attenuated BDNF expression and activation of extracellular signal‐regulated kinase (ERK) around PD 7. Moreover, plasticity‐related immediate early genes, which are transcriptionally regulated by BDNF‐ERK signaling, were also reduced by MS around PD 7. Interestingly, detailed analysis revealed that MS particularly reduced expression of BDNF gene and immediate early genes in the cornu ammonis 1 (CA1) of hippocampus at PD 7. Considering that BDNF‐ERK signaling is involved in spine formation, we next evaluated spine formation in the hippocampus during the weaning period. Our results show that MS particularly reduced mature spine density in proximal apical dendrites of CA1 pyramidal neurons at PD 21. These results suggest that MS could attenuate BDNF‐ERK signaling during primary synaptogenesis with a region‐specific manner, which is likely to lead to decreased spine formation and maturation observed in the hippocampal CA1 region. It is speculated that this incomplete spine formation during early brain development has an influence on learning capabilities throughout adulthood. Abstract : It still remains unclear how maternal separation (MS) affects neural circuit development. Here, we report that MS attenuated BDNF‐ERK signaling related to spine formation in the hippocampus during early brain development. Moreover, MS reduced dendritic spine density in the hippocampal CA1 region. These findings suggest that attenuation of BDNF‐ERK signaling by MS causes incomplete spine formation during primary synaptogenesis.